Key Technology of Relay Protection and Setting Calculation of Uhv Power Grid - Liu, Jinghui; Zhu, Guangze; Yang, Zhe; Xu, Zhen (International Journal of Mechanical and Electrical Engineering, 2024)
As the core component of the modern power transmission system, the stable operation of the UHV power grid is of great significance to ensure the overall safety of the power system. As a key line of defense in the ultra-high voltage power grid, relay protection can detect and isolate faults in time, thus limiting the impact of the accident to the minimum range. Setting calculation is an important basis for relay protection, which involves a series of complex calculation and analysis processes. This paper deeply analyzes the key technology of ultra high voltage power grid relay protection setting calculation, discusses the specific factors of the substation configuration on the setting calculation, carefully analyzes the principles of the setting calculation, comprehensively analyzes the related protection device configuration strategy, and further study the potential problems existing in the setting calculation and its effective countermeasures. Through the in-depth discussion and research of these key technical problems, it provides a set of scientific and reasonable norms and guidance methods for the relevant personnel in the setting and calculation of the relay protection of the ultra-high voltage power grid, so as to effectively guarantee the long-term stable operation and safe power supply of the power system.